Enhancing productivity of aromatic rice-chickpea paira cropping system through different nutrient management practices - Khanda, Chandramani; Nayak, Anshuman (ORYZA-An International Journal of Rice, 2023)
The field experiment was carried out at Regional Research and Technology Transfer Station, Bhawanipatna, Kalahandi of Odisha University of Agriculture & Technology, Bhubaneswar to evaluate the performance of three aromatic rice varieties under five different nutrient management practices during 2017-18 and 2018-19. The experiment was laid out in split-plot design taking three aromatic rice varieties (Geetanjali, Gangabali and Badshabhog) in main plot and five nutrient management practices (40:20:20, 60:30:30, 80:40:40 kg N:P2O5:K2O ha-1, 40:20:20 kg N:P2O5:K2O ha-1+ FYM 5 t ha-1  and 40:20:20  kg N:P2O5:K2O ha-1 + FYM 5 t ha-1 + Biofertilizers (Azospirillum and PSB 5 kg each ha-1 ) in sub- plot replicated thrice. Chickpea was sown as paira crop 15 days prior to the harvest of paddy. The yield attributes, yield and economics of production was maximum in aromatic rice Gangabali. Maximum grain yield was obtained with application of 80:40:40 kg N:P2O5:K2O ha-1(3480 kg ha-1) being at par with 40:20:20 kg N:P2O5:K2O ha-1 + FYM 5 t ha-1 (3303 kg ha-1) and 40:20:20  kg N:P2O5:K2O ha-1 + FYM 5 t ha-1 + Biofertilizers (3392 kg ha-1). The chickpea seed yield was maximum in Geetanjali (682 kg ha-1) grown plot, which was harvested fifteen days earlier than the other two varieties. The residual effect of nutrient management practices was prominent in the treatment where inorganic fertilizers were applied in conjunction with organic manures in which the seed yield of chickpea was 19-72% higher in the plots with combined application of organic manures and inorganic fertilizer than that of only inorganic fertilizers. The rice equivalent yield (REY), gross return, net return, return rupee-1 invested and partial factor productivity of NPK used were higher in Geetanjali. Among the nutrient management practices application of 40:20:20 kg N:P2O5:K2O ha-1  + FYM 5t ha-1 + Biofertilizer registered maximum REY (5088 kg ha-1), gross return (Rs.1,31,336 ha-1) and net return (Rs.75,868 ha-1) which was 43 and 24% higher than the plots treated with 40:20:20 kg N:P2O5:K2O ha-1 and  60:30:30 kg N:P2O5:K2O ha-1, respectively. The partial factor productivity of NPK used was significantly higher in the treatment supplied with less nutrients from inorganic and/or organics sources and gradually decreased with increasing NPK dose.